The Influence of the GASING Method on Basic Multiplication Concept Understanding in Third Grade Elementary School Students - La Ode Maharudin; Turmudi; Rina Heryani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The low level of understanding of basic multiplication concepts among elementary school students remains a recurring educational challenge in Indonesia. This study aims to examine the effect of the GASING (Easy, Fun, Enjoyable) method on third-grade students’ understanding of basic multiplication concepts. The study employed a quasi-experimental design with a nonequivalent control group, involving students from two schools selected through purposive sampling. The experimental class received instruction using the GASING method through structured stages, namely concrete, abstract, and mental calculation, while the control class received conventional instruction. Data were collected through essay tests and analyzed using N-Gain scores, t-tests, and Cohen’s d effect size. The results indicate that the experimental class achieved a significantly higher improvement in learning outcomes compared to the control class, with a high level of improvement and a large effect size. These findings imply that the GASING method can serve as an effective alternative instructional approach to enhance students’ understanding of multiplication concepts in elementary school, and has the potential to be more broadly integrated into primary mathematics teaching practices.